2022
DOI: 10.2147/jmdh.s384436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Overactive Bladder Symptoms in Patients Recovering from Post-Acute COVID-19 Syndrome

Abstract: Purpose Coronavirus disease (COVID-19) is a multi-organ viral infection with many manifestations. However, its impact on the genitourinary system is nowadays under investigation. This study aimed to evaluate the consequences on bladder function in patients suffering from post-acute COVID-19 syndrome (PACS) transferred to inpatient rehabilitation for long-term care after initial treatment for COVID-19 pathophysiology. Materials and Methods All the patients were initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
2
1
0
1
Order By: Relevance
“…In other populational studies from different countries the prevalence of moderate to severe LUTS is typically less than 25% considering the age distribution of our patients ( 23 25 ). We showed a predominance of storage symptoms in patients with long COVID, which is consistent with studies reporting on LUTS in the acute phase of COVID-19 ( 9 , 11 , 22 ) and also with the study from Zachariou et al, who found a high prevalence of overactive bladder among patients who had been hospitalized due to COVID-19 ( 14 ). Interestingly, we found minor differences between men and women and no impact of age in the prevalence of LUTS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other populational studies from different countries the prevalence of moderate to severe LUTS is typically less than 25% considering the age distribution of our patients ( 23 25 ). We showed a predominance of storage symptoms in patients with long COVID, which is consistent with studies reporting on LUTS in the acute phase of COVID-19 ( 9 , 11 , 22 ) and also with the study from Zachariou et al, who found a high prevalence of overactive bladder among patients who had been hospitalized due to COVID-19 ( 14 ). Interestingly, we found minor differences between men and women and no impact of age in the prevalence of LUTS.…”
Section: Discussionsupporting
confidence: 92%
“…However, the long-term effects of COVID-19 on LUTS have been poorly evaluated and the prevalence of LUTS in patients who recovered from COVID-19 remains unknown (12,13). In a study from Greece, a high prevalence of increased urinary frequency and urgency consistent with the diagnosis of overactive bladder has been reported in patients who were suffering with long COVID (14). The study did not evaluate the prevalence of LUTS in the population, since they only included 66 patients who reported having urinary urgency.…”
Section: Introductionmentioning
confidence: 99%
“…Athanasios Zachariou et al's 2022 study also resonates with our findings, reporting that 68.5% of patients with Post Acute Covid Syndrome experienced new or exacerbated urinary symptoms [22]. Our study's identification of the variety and frequency of incontinence symptoms, particularly urgency and postvoid dribbling, complements Zachariou's conclusion on the worsening of overactive bladder symptoms after COVID-19 infection.…”
Section: Discussionsupporting
confidence: 89%
“…nos demuestra también que la vejiga hiperactiva puede contribuir en el síndrome postagudo de COVID-19 demostrando la presencia de síntomas post COVID-19 en 46 de 147 pacientes evaluados en donde se dividieron en dos grupos distintos; En el grupo A se incluyeron a 44 pacientes con el diagnostico reciente de vejiga hiperactiva post-COVID y en el grupo B a 22 pacientes con síntomas de vejiga hiperactiva que empeoraron. En donde en ambos grupos se encontró una disminución de la calidad de vida 8 . Esto demuestra que en aquellos pacientes con el diagnóstico de COVID-19 pueden desarrollar síntomas urinarios ya sea con el antecedente de vejiga hiperactiva e incluso con aparición de síntomas de Novo.…”
Section: Tabla No 1 Datos Demográficos De La Población De Estudiounclassified